2012
DOI: 10.1016/j.atmosenv.2011.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Air quality diagnosis from comprehensive observations of total OH reactivity and reactive trace species in urban central Tokyo

Abstract: a b s t r a c tWe have conducted a comprehensive observational study to determine the mixing ratios of atmospheric chemical species and total OH reactivity in central Tokyo, in order to diagnose the air quality during summer and winter 2007 and autumn 2009. Concentrations of over 70 reactive trace species were continuously measured throughout each season. The total OH reactivity was measured directly using a laser-induced pump and probe technique. The observed chemical species exhibited seasonal variations. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 29 publications
12
29
0
Order By: Relevance
“…In contrast, there were no noticeable differences in CO levels between the urban and rural sites (∼ 1-2 ppm). The observed CO, NO x , and SO 2 levels in TRF were much lower than those observed in the suburban regions of Chinese megacities such as Beijing , Shanghai (Tie et al, 2013), and the Pearl River Delta region and similar to the observed levels in Tokyo, Japan (Yoshino et al, 2012).…”
Section: Observational Resultssupporting
confidence: 73%
“…In contrast, there were no noticeable differences in CO levels between the urban and rural sites (∼ 1-2 ppm). The observed CO, NO x , and SO 2 levels in TRF were much lower than those observed in the suburban regions of Chinese megacities such as Beijing , Shanghai (Tie et al, 2013), and the Pearl River Delta region and similar to the observed levels in Tokyo, Japan (Yoshino et al, 2012).…”
Section: Observational Resultssupporting
confidence: 73%
“…OH reactivity for the sum of CO, NO, NO y , O 3 , SO 2 and methane is assigned as "inorganics" and that for NMHCs except for biogenic species (isoprene and monoterpenes) is assigned as "anthropogenic". Averaged total OH reactivity at MEF is much lower than that measured in urban (33.4 s À1 ) and suburban (27.7 s À1 ) areas in Tokyo in the same summer season (Yoshino et al, 2006(Yoshino et al, , 2012 using techniques that are the same as that used at MEF for this study. Measurements of OH reactivity in the boreal forest in summer have been reported (Sinha et al, 2010) and the averaged total OH reactivity (9 s À1 ) was similar to that derived from the present study.…”
Section: Contribution To the Oh Reactivitymentioning
confidence: 71%
“…Recently, OH reactivity has been recognized as a useful index for the observation of trace species in ambient air. The results of the measurements of OH reactivity and comparison with the trace species analysis have been reported for some environmental conditions (Sadanaga et al, 2004;Yoshino et al, 2006Yoshino et al, , 2012Ingham et al, 2009;Mao et al, 2009;Lee et al, 2009;Sinha et al, 2008Sinha et al, , 2010Kim et al, 2011, Nakashima et al, 2010. OH reactivity measurements have been reported for several forests which the concentration of isoprene (Di Carlo et al, 2004;Ingham et al, 2009;Sinha et al, 2008;Edwards et al, 2013) and that of monoterpenes (Sinha et al, 2010;Nölscher et al, 2012) is predominant.…”
Section: Introductionmentioning
confidence: 98%
“…High OH reactivity has also been observed in Paris during the MEGAPOLI campaign in 2010, with k OH reaching 130 s −1 for continental air masses and calculations based on measured VOC concentrations underestimating the reactivity by up to 75 % (Dolgorouky et al, 2012). Reactivity measurements in Tokyo were underestimated in summer, spring and autumn, but reproduced to within 5 % in winter, with the reactivity correlating well with NO x throughout the year (Sadanaga et al, 2004b;Yoshino et al, 2006;Chatani et al, 2009;Yoshino et al, 2012). Aircraft measurements of OH reactivity have also shown that reactivity tends to decrease with altitude, with discrepancies between observed and calculated reactivity most pronounced at altitudes up to 2 km and tending towards agreement at altitudes above 4 km (Mao et al, 2009).…”
Section: Overcome This Issuementioning
confidence: 89%